Advanced imaging improves prediction of hemorrhage after stroke thrombolysis. Issue 4 (26th February 2013) - Campbell, Bruce C. V.; Christensen, Søren; Parsons, Mark W.; Churilov, Leonid; Desmond, Patricia M.; Barber, P. Alan; Butcher, Kenneth S.; Levi, Christopher R.; De Silva, Deidre A.; Lansberg, Maarten G.; Mlynash, Michael; Olivot, Jean‐Marc; et al.
<x xml:space="preserve">Abstract</x> Objective Very low cerebral blood volume (VLCBV), diffusion, and hypoperfusion lesion volumes have been proposed as predictors of hemorrhagic transformation following stroke thrombolysis. We aimed to compare these parameters, validate VLCBV in an independent cohort using DEFUSE study data, and investigate the interaction of VLCBV with regional reperfusion. Methods The EPITHET and DEFUSE studies obtained diffusion and perfusion magnetic resonance imaging (MRI) in patients 3 to 6 hours from onset of ischemic stroke. EPITHET randomized patients to tissue plasminogen activator (tPA) or placebo, and all DEFUSE patients received tPA. VLCBV was defined as cerebral blood volume<2.5th percentile of brain contralateral to the infarct. Parenchymal hematoma (PH) was defined using European Cooperative Acute Stroke Study criteria. Reperfusion was assessed using subacute perfusion MRI coregistered to baseline imaging. Results In DEFUSE, 69 patients were analyzed, including 9 who developed PH. The >2 ml VLCBV threshold defined in EPITHET predicted PH with 100% sensitivity, 72% specificity, 35% positive predictive value, and 100% negative predictive value. Pooling EPITHET and DEFUSE (163 patients, including 23 with PH), regression models using VLCBV (p<0.001) and tPA (p=0.02) predicted PH independent of clinical factors better than models using diffusion or time to maximum>8 seconds lesion volumes. Excluding VLCBV in regions without reperfusion improved specificity from 61 to 78% in the pooled analysis. Interpretation VLCBV predicts PH after stroke thrombolysis and appears to be a more powerful predictor than baseline diffusion or hypoperfusion lesion volumes. Reperfusion of regions of VLCBV is strongly associated with post‐thrombolysis PH. VLCBV may be clinically useful to identify patients at significant risk of hemorrhage following reperfusion. ANN NEUROL 2013;73:510–519